Expertise differences in movement switching in kendo players - Usui, N.; Okumura, M.; Kudo, K. (International Journal of Sport & Health Science, 2018)
To succeed in many sports, players must not only adjust their movements during execution in response to environmental changes, but also switch to different movements altogether. Previous studies have implicated executive functions in movement switching ability. We aimed to clarify expertise differences in movement adjustment and switching, and compared performance on three tasks of target striking between expert and intermediate kendo players as participants. Task 1 was a simple strike, whereby participants struck targets at one position; Task 2 was an adjusted strike, whereby participants struck targets at three positions in a random order. Task 3 was strike-defense switching, whereby participants struck targets as in Task 2 while were also required to switch to defense when an opponent made a counter-strike. That is, the participants were required accurate strike in Task 1 and 2 close to the kendo practices, and were required accurate strike and defense in Task 3 close to the real matches. We found no differences in strike movement time and accuracy in any of the tasks between groups. However, expert players were able to execute successful strike-defense switching in Task 3, whereas intermediate players were not. These results suggest that an expertise difference exists in executive functions, and that it is essential for players to practice focused on acquisition of switching skills in order to further improve their performance.